Reduction in fracture rates with Denosumab compared to Alendronate in treatment naïve patients: a propensity-matched ‘real world’ cohort and instrumental variable analysis. - Khalid, S; Ali, M; Judge, A; Arden, N; van Staa, T; Cooper, C; Javaid, M; Prieto-Alhambra, D (Springer, 2017)
To compare the risk of hip and all osteoporotic fracture/s observed amongst treatment naïve users of subcutaneous denosumab and oral alendronate.